1995
DOI: 10.1073/pnas.92.11.4862
|View full text |Cite
|
Sign up to set email alerts
|

Continuous activation of gp130, a signal-transducing receptor component for interleukin 6-related cytokines, causes myocardial hypertrophy in mice.

Abstract: To investigate the physiological roles of gpl30 in detail and to determine the pathological consequence of abnormal activation of gpl30, transgenic mice having continuously activated gpl30 were created. This was carried out by mating mice from interleukin 6 (IL-6) and IL-6 receptor (IL-6R) transgenic lines. Offspring overexpressing both IL-6 and IL-6R showed constitutive tyrosine phosphorylation of gpl30 and a downstream signaling molecule, acute phase response factor/signal transducer and activator of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
260
1
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(278 citation statements)
references
References 49 publications
11
260
1
6
Order By: Relevance
“…Experimental induction of hemodynamic overload in the adult mammalian heart has been shown to provoke a transient increase in pro-inflammatory cytokines (2). Furthermore, cardiac-specific over expression of IL-6 and TNF-α in mice hearts has been shown to develop cardiac hypertrophy and ventricular dysfunction similar to that seen in human disease conditions, suggesting that cytokines are critically involved in the cardiac remodeling process (9,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental induction of hemodynamic overload in the adult mammalian heart has been shown to provoke a transient increase in pro-inflammatory cytokines (2). Furthermore, cardiac-specific over expression of IL-6 and TNF-α in mice hearts has been shown to develop cardiac hypertrophy and ventricular dysfunction similar to that seen in human disease conditions, suggesting that cytokines are critically involved in the cardiac remodeling process (9,30).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned cytokines play a dual role, activating apoptosis in myocytes (13), while also functioning in a cytoprotective manner (15). Furthermore, inappropriate activation of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) have been recognized as an important mediator in the development of endothelial dysfunction, cardiac hypertrophy, and heart failure in experimental animal models and in humans (9,17,28,30). Atrial natriuretic peptide (ANP) has been shown to inhibit the TNF-α induced adhesion molecule expression in endothelial cells (32).…”
Section: Introductionmentioning
confidence: 99%
“…gp130 also forms part of the receptor-complexes of LIF, OSM, CNTF, IL-11 (Gearing et al, 1992;Ip et al, 1992;Liu et al, 1992;Taga et al, 1992;Fourcin et al, 1994), as well as CT-1 (Pennica et al, 1995). Targeted disruption of gp130 in mice is lethal during early embryogenesis due to impaired myocardial development and hematopoiesis (Yoshida et al, 1996), whereas continuous activation of gp130 in mice transgenic for both IL-6 and the ILdR causes myocardial hypertrophy (Hirota et al, 1995).…”
Section: Structure Of the Interleukin-6 Receptor And Gp130mentioning
confidence: 99%
“…and IL-6 receptor in the hearts of transgenic mice was shown to be associated with ventricular hypertrophy and increased JAK/ STAT3 activity (16). Thus, we sought to determine whether CT-1 is also able to activate STAT3 kinase.…”
Section: Pd098059 Does Not Block the Activation Of The Stat3mentioning
confidence: 99%